Superparamagnetic Iron Oxide Nanoparticles and Static Magnetic Field Regulate Neural Stem Cell Proliferation - Li, Dan; Hu, Yangnan; Wei, Hao; Chen, Wei; Liu, Yun; Yan, Xiaoqian; Guo, Lingna; Liao, Menghui; Chen, Bo; Chai, Renjie; Tang, Mingliang (Frontiers in Cellular Neuroscience, 2022)
Neural stem cells (NSCs) transplantation is a promising approach for the treatment of various neurodegenerative diseases. Superparamagnetic iron oxide nanoparticles (SPIOs) are reported to modulate stem cell behaviors and used for medical imaging. However, the detailed effects of SPIOs under the presence of static magnetic field (SMF) on NSCs are not well elucidated. In this study, it was found that SPIOs could enter the cells within 24 h, while they were mainly distributed in the lysosomes. SPIO exhibited good adhesion and excellent biocompatibility at concentrations below 500 μg/ml. In addition, SPIOs was able to promote NSC proliferation in the absence of SMF. In contrast, high intensity of SMF (145±10 mT) inhibited the expansion ability of NSCs. Our results demonstrate SPIOs with SMF could promote NSC proliferation, which could have profound significance for tissue engineering and regenerative medicine for SPIO applications.